Exploring factors influencing financial planning after retirement: structural equation modeling approach - Jalil, Md. Abdul; Abdul Razak, Dzuljastri; Azam, Ferdous (Science Publications, 2013)
The study explores the critical factors that influence financial planning after retirement among Malaysians, an area which has somewhat been largely overlooked by the extant literature. The study has used a quantitative method to survey a sample of 170 Malaysian citizens, from various places in the Klang Valley area. Exploratory factor analysis, confirmatory factor analysis and structural equation modeling were used to analyze the data. The results suggest that the paths are interrelated to the casual processes significantly. Furthermore, individual’s income or monthly salary is found to be the most important factor influencing financial planning, followed by attitude and culture. The results are mainly favourable to academics and practitioners in Malaysia by contributing an understanding into critical factors that influence people to make financial plan before their retirement. The study provides implications of the findings in the concluding section.